Experience of compiling of geomorphological map scale 1:1.000.000 by morphogenetic principle (for continental part of Vietnam) - An, Lê Đức; Khanh, Uông Đình; Thịnh, Võ; Dũng, Bùi Quang (Vietnam Journal of Earth Sciences, 2014)
This type of map is compiled with the aim of serving the integrated geographical studies and other field. The main contents of the map are the morphogenetic types of relief. The map legend composes of 4 parts: I. The morphogenetic types of relief; II. Landforms; III. The age of relief; IV. The other symbols. The morphogenetic types of relief being the main contents are showed on the map by the color background. They consist of 29 units, and gather in 9 groups, 2 series. The layering of relief is reflected on the map by letters: a, b, c, d, e, f, g. Landforms classified according to their genesis are showed on the map by the non-scale symbols, superimposing on the color background of types of relief. There are 10 genetic groups of landform: tectonic and denudation-structure, general denudation, fluvial, gravity, dissolve-absorption, karst, marine, wind, biological, anthropogenic. The age of relief showed by letters and figures as in geology is superimposed on the types of relief, and composes of: Neogene (N), Miocene (N1), Pliocene (N2), Quaternary (Q), Pleistocene (Q1), Early Pleistocene (Q1 1), Holocene (Q2),... Other symbols indicate the elements out of landforms, such as lithology, boundary,... The topographical basis is simplified. This map fairly well expresses the morphology of relief, as well as all factors of landform-formation of territory, will be the good basis for landscape, pedology, soil erosion, environment conservation,... studies, and other works of territorial planning for different purposes (forestry, agriculture, communication,...).